Ceramsite production using water treatment residue as main ingredient: The key affecting factors identification. (15th April 2022) - Wang, Changhui; Huang, Chenghao; Xu, Huacheng; Yuan, Nannan; Liu, Xin; Bai, Leilei; He, Xiaosong; Liu, Rui
Abstract: As an inevitable by-product of potable water production, drinking water treatment residue (DWTR) recycling to make ceramsite can provide both environmental and economic benefits in constructing filtration treatment system for water environment remediation. Given the varied properties of DWTR from different waterworks, this study aims to identify the key factors affecting ceramsite production from DWTR as main ingredient based on five different DWTR with using clay as the auxiliary material. The results showed that of sintering temperature (500–1000 °C), DWTR:clay ratio (5:5 to 9:1), sintering time (5–60 min), and granule diameter (5–15 mm), the sintering temperature was the key parameter. Increasing temperatures from 500 to 1000 °C gradually promoted DWTR sintering by enhancing Si and Al crystallization, which typically increased the formation of SiO2 and CaAl2 Si2 O8 crystals in ceramsite. Ceramsites made from different DWTR tended to have different properties, mainly resulting from varied contents of Si (20.2%–48.6%), K (0.0894%–2.39%), Fe (4.56%–14.3%), and loss on ignition (11.7%–39.5%). During ingredients preparation to produce up-to-standard ceramsite, supplying additional Si and diluting loss on ignition were necessary for all DWTR, while supplying K and diluting Fe may be required for specific DWTR, due to the potential varied DWTR compositions caused by different water production processes applied (e.g., type of flocculants). Further toxicity characteristic leaching procedure analysis indicated the increased leaching of Cu. However, DWTR based ceramsite was identified as non-hazardous material; even, sintering treatment reduced the leachability of Ba, Be, Cd, and Cr. DWTR based ceramsite also had relatively high specific surface area (22.1–50.5 m 2 /g) and could adsorb Cd, Cu, and Pb from solution. Overall, based on appropriate management, DWTR can be recycled as the main ingredient in the production of ceramsite for water environment remediation. Graphical abstract: Image 1 Highlights: Factors affecting ceramsite made from water treatment residue (DWTR) were studied. Higher sintering temperature promoted SiO2 /CaAl2 Si2 O8 producing to make ceramiste. Varied Si, K, Fe, and loss on ignition (LOI) of DWTR regulated ceramsite property. Supplying Si and diluting LOI to DWTR was necessary for ingredients preparation. DWTR based ceramiste was non-hazardous and feasible to adsorb Cd, Cu, and Pb.